SpBark Suppresses Bacterial Infection by Mediating Hemocyte Phagocytosis in an Invertebrate Model, Scylla paramamosain - Li, Xin-Cang; Zhou, Jian; Zhou, Jun-Fang; Wang, Yue; Ma, Hongyu; Wang, Yuan; Zhao, Shu; Fang, Wen-Hong (Frontiers in Immunology, 2019)
Scavenger receptors are cell surface membrane-bound receptors that typically bind multiple ligands and promote the removal of endogenous proteins and pathogens. In this study, we characterized a novel scavenger receptor-like protein, namely, SpBark. SpBark was upregulated in hemocytes after challenges with bacteria, suggesting that it might be involved in antibacterial defense. SpBark is a type I transmembrane protein with four extracellular domains, including three scavenger receptor cysteine-rich domains (SRCRDs) and a C-type lectin domain (CTLD). Western blot assay showed that SpBark CTLD possessed a much stronger binding activity to tested microbes than the three SRCRDs. It also exhibited apparent binding activities to lipopolysaccharide (LPS) and acetylated low-density lipoprotein (ac-LDL), whereas the other SRCRDs showed much lower or no binding activities to these components. Agglutination activities were observed in the presence of Ca2+ by incubating microorganisms with SpBark CTLD instead of SRCRDs. These results suggested that SpBark CTLD was the major binding site for ac-LDL and LPS. Coating Vibrio parahemolyticus with SpBark CTLD promoted bacterial clearance in vivo. This finding indicated that SpBark might participate in the immune defenses against Gram-negative bacteria through a certain mechanism. The promotion of bacterial clearance by SpBark was further determined using SpBark-silenced crabs injected with V. parahemolyticus. SpBark knockdown by injection of SpBark dsRNA remarkably suppressed the clearance of bacteria in hemolymph. Meanwhile, it also severely restrained the phagocytosis of bacteria. This finding suggested that SpBark could modulate the phagocytosis of bacteria, and the promotion of bacterial clearance by SpBark was closely related to SpBark-mediated phagocytosis activity. The likely mechanism of bacterial clearance mediated by SpBark was as follows: SpBark acted as a pattern recognition receptor, which could sense and bind to LPS on the surface of invading bacteria with its CTLD in hemolymph. The binding to LPS made the bacteria adhere to the surface of hemocytes. This process would facilitate phagocytosis of the bacteria, resulting in their removal. This study provided new insights into the hemocyte phagocytosis mechanisms of invertebrates and the multiple biological functions of Bark proteins.